2010
DOI: 10.1097/hpc.0b013e3181e9d410
|View full text |Cite
|
Sign up to set email alerts
|

“Call 911” STEMI Protocol to Reduce Delays in Transfer of Patients From Non Primary Percutaneous Coronary Intervention Referral Centers

Abstract: Primary percutaneous coronary intervention (PPCI) is the preferred method of reperfusion for ST-segment elevation myocardial infarction (STEMI), if it can be performed in a timely manner by an experienced interventional cardiologist at a high volume STEMI Receiving Center. However, an estimated 50% of STEMI patients present to STEMI Referral Centers without PPCI capability. Transfer of STEMI patients for PPCI has been shown to improve outcomes as compared with fibrinolysis given at the presenting hospital. Non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…This adds to the prior single‐center pilot study that demonstrated a reduction in median FMC2B by 50%, from 167.5 to 88.5 minutes after implementation of the Call 911 protocol 19. Similarly, Tennyson et al 27 evaluated the use of the municipal 911 ALS ambulance service compared with a contracted private ambulance service for STEMI IFTs from a single community hospital to a tertiary care center.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This adds to the prior single‐center pilot study that demonstrated a reduction in median FMC2B by 50%, from 167.5 to 88.5 minutes after implementation of the Call 911 protocol 19. Similarly, Tennyson et al 27 evaluated the use of the municipal 911 ALS ambulance service compared with a contracted private ambulance service for STEMI IFTs from a single community hospital to a tertiary care center.…”
Section: Discussionmentioning
confidence: 95%
“…A prior pilot study at a single PCI-capable center within the Los Angeles (LA) County regional cardiac system demonstrated the use of 911 for interfacility STEMI transfers to be both safe and feasible, resulting in a 50% reduction in median FMC2B time. 19 In the current study, we evaluated the FMC2B time for patients with STEMI after implementation of a "Call 911" protocol for STEMI IFTs across the entire regional system.…”
mentioning
confidence: 99%
“…Multiple strategies hold promise. For example, activating EMS transportation prior to PCI center activation, 24 using the 911 system to transfer patients, 25 using operations research tools to enhance the operational flexibility of the ED, 26,27 enhancing regionalization efforts to reduce EMS response times, 28,29 standardizing the initial interaction with EMS (eg, patient staying on the stretcher), 24 enhancing hospital-EMS relationships, 22 and appropriate use of ground-based (rather than helicopter) EMS. 19,20 …”
Section: Discussionmentioning
confidence: 99%
“…In Turkey, to date, no investigations into the medical transport-chain and transport durations have been conducted. In addition, it was recently reported that the development of city-wide transport protocols and the establishment of hospital networks could shorten pain-to-balloon time in some countries (25)(26)(27)(28)(29)(30). In contrast, in Turkey, no transport-chain protocol has been proposed by the municipality or health ministry.…”
Section: Discussionmentioning
confidence: 99%